Ekonomi Syariah: Menjawab Strategi Pemulihan Ekonomi Pasca Pandemi (TAWAZUN: Journal of Sharia Economic Law, 2022)
The Covid-19 pandemic had a considerable influence, particularly in economic spheres. The occurrence of problems such as layoffs, unemployment, rising poverty rates, and economic growth is seldom enough to necessitate a remedy. The goal of this research is to see how Islamic economics might help with post-pandemic economic recovery. This research employs a qualitative descriptive approach, as well as content analysis and a literature review (library research). Secondary data was obtained from the institution's official website. The study's findings show that Islamic economics, when combined with the framework of the national economy, makes a positive contribution to dealing with and improving post-pandemic economic conditions, including: (a) special instruments that can protect vulnerable groups of people, such as philanthropic models of zakat management, infaq, waqf, shodaqoh, and tafakul; (b) philanthropic models of zakat management, infaq, (b) Islamic financial development features and tools that assist and recover the UMKM sector through risk-sharing economic growth and prosperity, as well as simpler processes that increase social welfare. c) Capital development and distribution as a means of reviving the green economy (green economy). The growth of Islamic financial assets, such as Islamic banking, Islamic IKNB, and Islamic capital markets, has made a significant contribution to the national economy's structure.